NMR Hyperpolarization Techniques for Biomedicine. Issue 8 (3rd December 2014) - Nikolaou, Panayiotis; Goodson, Boyd M.; Chekmenev, Eduard Y.
Abstract: Recent developments in NMR hyperpolarization have enabled a wide array of new in vivo molecular imaging modalities, ranging from functional imaging of the lungs to metabolic imaging of cancer. This Concept article explores selected advances in methods for the preparation and use of hyperpolarized contrast agents, many of which are already at or near the phase of their clinical validation in patients. Abstract : Loading image : Recent developments in NMR hyperpolarization have enabled a wide array of new in vivo molecular imaging modalities, ranging from functional imaging of the lungs to metabolic imaging of cancer. Explored are selected advances in methods for the preparation and use of hyperpolarized contrast agents, many of which are already at the phase of their clinical validation in patients.